Wettability, structural and optical properties investigation of TiO2 nanotubular arrays - Zalnezhad, E.; Maleki, E.; Banihashemian, S.M.; Park, J.W.; Kim, Y.B.; Sarraf, M.; Sarhan, Ahmed Aly Diaa Mohammed; Ramesh, Singh (Elsevier, 2016)
In this study, the effect of microstructural evolution of TiO2 nanotubular arrays on wettability and optical properties was investigated. Pure titanium was deposited on silica glass by PVD magnetron sputtering technique. The Ti coated substrates were anodized in an electrolyte containing NH4F/glycerol. The structures of the ordered anodic TiO2 nanotubes (ATNs) as long as 175 nm were studied using field emission scanning electron microscopy (FESEM) and X-ray diffraction (XRD). The result shows a sharp peak in the optical absorbance spectra around the band gap energy, 3.49–3.42 eV for annealed and non-annealed respectively. The thermal process induced growth of the grain size, which influence on the density of particles and the index of refraction. Furthermore, the wettability tests' result displays that the contact angle of intact substrate (θ = 74.7°) was decreased to 31.4° and 17.4° after anodization for amorphous and heat treated (450 °C) ANTs coated substrate, respectively.